(untitled) (Fiep Bulletin - online, 2011)
The aim of the present study was to analyze the association between reaction time and movement time in adults. The reaction time was measured using a platform containing six recipients numbered 1-6 and a control panel linked to a computer, composed of two diodes that provided visual stimulus to initiate the task and an answer key to register the measures of time. The task was to carry tennis balls from the bottom of the platform to the top in the following order (4-1/5-2/6-3) in the highest possible speed. It was interpreted as the reaction period the time between the presentation of the stimulus and the released of the hand of the response-key to start the task. The movement time was measured from the release of the key up to the time that that the subject placed the balls in the pre-determined sequence and pressed the key again, characterizing thus the end of task. The subjects were 10 adults of both genders, aged between 18 and 35 years with no previous experience in the task. For the statistical analysis it was used Pearson’s product-movement correlation test which detected significant value for the association of RT and MT (r=0,71; p=0,021). The results indicate significant correlation between RT and MT with adults.